Conflict Reality of the Implementation of Ngabul Village Market Relocation Policy - Amri, Syaiful; Soesilowati, Etty; Arsal, Thriwaty (JESS (Journal of Educational Social Studies), 2019)
The Ngabul market relocation in the process of implementation caused social problems, the majority of market traders who were members of the Ngabul market traders association rejected the policy. This study aims to analyze the occurrence of conflict in the process of implementing the market relocation policy of the Annual District of Ngabul in Jepara Regency. This study uses a qualitative approach. The technique of collecting data through in-depth interview, observation and document study. The data analysis in this study used Spradley model analysis techniques, including domain analysis, taxonomic analysis, compound analysis, and analysis of cultural themes. The results showed that the conflict in the implementation process of Ngabul market relocation policy was caused by differences of opinion between related parties, communication problems, and differences in the disposition of policy implementers with market traders, village authorities continued to develop new markets, after the market was inaugurated, the majority of market traders long time they maintain their attitude not to occupy new markets and they prefer to sell in the emerging market that is built with self-financing on land owned by residents. The findings of this study are the reality of the causes of conflict in the implementation of Ngabul village market relocation policy can be categorized into Ralf Dahrendorf's conflict theory. The reality of the conflict cannot be separated from the theory of Edward III's policy implementation. The benefits of the findings of this study can be used as a reference for the preparation of strategic steps in solving the problem of market relocation.